Mediterranean Islands and the Challenge of Innovation: Learning From the Case of the Chinese Province of Hainan - Goulard, Sebastien (Mediterranean Journal of Social Sciences, 2012)
Mediterranean islands heavily depend on tourism as their main economic resources. This development path has taken overfrom a poorly industrialized, agricultural society, and has insured economic integration to these islands. However, Mediterranean insularregions still suffer from a number of developmental issues leading to economic retardation vis-Ã -vis continental regions. Tourism hasstrengthened their peripheral status. Hainan, an insular province of China has experienced a similar situation. However, although tourismstill remains a major economic resource for Hainan, new policies have been implemented to diversify the local economy and developinnovation-led activities on the island. Traditionally, peripheral regions are not considered as innovative regions because of severalobstacles (e.g.: remoteness, social particularisms) (Soete, 1997). To be efficient, innovative policies should not only support technologyand research, but also other economic aspects of the innovation process (Landabaso, 2003). Does it mean that decentralization isrequired to transform peripheral islands into innovative society? Or is the central government more likely to implement innovativepolicies? This paper will attempt to explore the several paths followed by Hainan to develop innovation, draw the limits of this policy, andquestion whether or not similar measures may be adopted by Mediterranean islands. The author argues that development of a privatesector is the key factor for innovation in insular territories.